Soft Skill Development Through Career Counseling Programs to Face The Challenges of The Work Industry for Students - Nur Inyatun Nisa (Green Publisher Indonesia, 2025)
This article aims to examine and understand the development of students' soft skills through career counseling programs so that they can be better prepared to face challenges in the work industry. The approach method used in this study is library research with a descriptive analysis method. Researchers collected data from a variety of written sources, including articles, theses, relevant journals, books, and documents, as well as online sources with a focus on keywords such as